Internalizing Islamic Education Values in Saman Dance as Acehnese Cultural Heritage: Efforts to Shape the Character of the Young Generation in the Digital Era. - Teuku Muhammad Husni; Ichsan; Berlian Denada (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The rapid development of digital technology has brought significant changes to the values, lifestyles, and behaviors of the younger generation, creating challenges for Islamic character education. One strategic effort to address this issue is by utilizing local cultural heritage as a medium for value internalization. This study aims to analyze the internalization of Islamic educational values embedded in the Saman Dance as an intangible cultural heritage of Aceh and its contribution to strengthening the character of the younger generation in the digital era. The study employed a qualitative approach through library research supported by content analysis. Data were collected from scientific journal articles, books, official documents, and relevant literature concerning Islamic education, character education, local wisdom, and the Saman Dance. The findings reveal that the Saman Dance embodies various Islamic educational values, including religiosity, discipline, responsibility, cooperation, mutual respect, leadership, sincerity, and social solidarity. These values are internalized through synchronized movements, poetic lyrics containing Islamic messages, collective learning processes, and the ethical norms practiced during performances. Furthermore, the integration of Islamic values with local cultural traditions offers an innovative and contextual model of character education that is relevant to the challenges faced by today's youth. The study concludes that the Saman Dance functions not only as a cultural performance but also as an effective educational medium for strengthening Islamic character while preserving Acehnese cultural identity amid the rapid transformation of the digital era.